2020
DOI: 10.3390/ijerph17155326
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Students Meeting Components of Canada’s New 24-Hour Movement Guidelines over Time in the COMPASS Study

Abstract: This study aimed to determine if secondary school students are meeting the new Canadian 24-Hour Movement Guidelines (24-MG), as well as each individual recommendation (physical activity; sleep; sedentary behavior) within the 24-MG, and which student-level characteristics predict meeting the 24-MG, both cross-sectionally and longitudinally. This study is the first to examine longitudinal changes in students meeting the 24-MG, as well as student-level characteristics that were predictive of favourable shifts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…The adherence to 24-Hour Movement Guidelines found in our study is higher than those found in the studies conducted with European [ 17 , 19 , 27 ] and Asian adolescents [ 14 , 21 , 26 ] and lower than several studies conducted in the United States (5.0%–9.4%) [ 16 , 22 , 23 ]. However, our results are similar to the results found in Canadian adolescents [ 15 , 18 , 28 , 29 , 30 , 31 , 32 , 33 ]. These results underline the importance of addressing these movement behaviours from an integrative and holistic approach to increase physical activity and sleep duration and decrease screen time [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The adherence to 24-Hour Movement Guidelines found in our study is higher than those found in the studies conducted with European [ 17 , 19 , 27 ] and Asian adolescents [ 14 , 21 , 26 ] and lower than several studies conducted in the United States (5.0%–9.4%) [ 16 , 22 , 23 ]. However, our results are similar to the results found in Canadian adolescents [ 15 , 18 , 28 , 29 , 30 , 31 , 32 , 33 ]. These results underline the importance of addressing these movement behaviours from an integrative and holistic approach to increase physical activity and sleep duration and decrease screen time [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, most existing studies have reported that less than 10% of adolescents met the 24-Hour Movement Guidelines [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. These aforementioned studies have found inconsistent results in the proportion of adolescents who meet the 24-Hour Movement Guidelines, which have ranged from 0.3% to 2.0% in Asian [ 14 , 21 , 26 ] 3.1% in South Americans [ 25 ], 2.2% to 9.4% in North Americans (ranging from 2.2% to 5.2% in Canadian and from 5.0% to 9.4% in American) [ 4 , 15 , 16 , 18 , 22 , 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ], and from 1.7% to 2.2% in European [ 17 , 19 , 27 ]. Most adolescents met sleep duration recommendations [ 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 25 ,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of meeting screen use recommendations in the current sample of Alaskan adolescents is much higher (>50%) compared to that among other population-based studies. For example, using the Canadian COMPASS survey, only 6.4% of students within grade 9 met screen use recommendations [38]. It is unclear why the prevalence of meeting screen use recommendations in Alaskan adolescents is so much higher than that among other populations.…”
Section: Discussionmentioning
confidence: 99%